Closing the Gap: Safeguarding Participants' Rights by Expanding the Federal Common Law of ERISA - Jayne Elizabeth Zanglein (Washington University Law Quarterly, 1994)
This Article will explore the current boundaries of the federal common law of ERISA and will urge the expansion of these boundaries to protect plan participants who have been betrayed without a remedy.
Keywords: Qualified benefit plans; Employee Retirement Income Security Act of 1974; United States; Employee fringe benefits; Federal preemption (Labor law); Insurance crimes; Bad faith (Law); Contracts